Altering singlet fission pathways in perylene-dimers; perylene-diimide versus perylene-monoimide - Papadopoulos, Ilias; Gutierrez-Moreno, David; Bo, Yifan; Casillas, Ruben; Greißel, Phillip; Clark, Timothy; Fernandez-Lazaro, Fernando; Guldi, Dirk Michael (Nanoscale, 2022)
We used a systematic approach to shed light on the inherent differences in perylenes, namely monoimides versus diimides, including coplanarity and dipole moment, and their impact on singlet fission (SF) by designing, synthesizing, and probing a full fledged series of phenylene- and naphthalene-linked dimers. Next to changing the functionality of the perylene core, we probed the effect of the spacers and their varying degrees of rotational freedom, molecular electrostatic potentials, and intramolecular interactions on the SF-mechanism and -efficiencies. An arsenal of spectroscopic techniques revealed that for perylene-monoimides, a strong charge-transfer mixing with the singlet and triplet excited states restricts SF and yields low triplet quantum yields. This is accompanied by an up-conversion channel that includes geminate triplet-triplet recombination. Using perylene-diimides alters the SF-mechanism by populating a charge-separated-state intermediate, which either favors or shuts-down SF. Napthylene-spacers bring about higher triplet quantum yields and overall better SF-performance for all perylene-monoimides and perylene-diimides. The key to better SF-performance is rotational freedom because it facilitates the overall excited-state polarization and amplifies intramolecular interactions between chromophores.
CRIS-Team WoS Importer:2022-04-08

Controlling Interchromophore Coupling in Diamantane-Linked Pentacene Dimers To Create a “Binary” Pair - Greißel, Phillip; Schroeder, Zachary W.; Thiel, Dominik; Ferguson, Michael J.; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Journal of the American Chemical Society, 2024)
Two isomeric pentacene dimers, each linked by a diamantane spacer, have been synthesized. These dimers are designed to provide experimental evidence to support quantum mechanical calculations, which predict the substitution pattern on the carbon-rich diethynyldiamantane spacer to be decisive in controlling the interpentacene coupling. Intramolecular singlet fission (i-SF) serves as a probe for the existence and strength of the electronic coupling between the two pentacenes, with transient absorption spectroscopy as the method of choice to characterize i-SF. 4,9-Substitution of diamantane provides a pentacene dimer (4,9-dimer) in which the two chromophores are completely decoupled and that, following photoexcitation, deactivates to the ground state analogous to a monomeric pentacene chromophore. Conversely, 1,6-substitution provides a pentacene dimer (1,6-dimer) that exhibits sufficiently strong coupling to drive i-SF, resulting in correlated triplet M(T1T1) yields close to unity and free triplet (T1 + T1) yields of ca. 50%. Thus, the diamantane spacer effectively switches “on” or “off” the coupling between the chromophores, based on the substitution pattern. The binary control of diamantane contrasts other known molecular spacers designed only to modulate the coupling strength between two pentacenes.
CRIS-Team Scopus Importer:2024-04-19

Deep-Saddle-Shaped Nanographene Induced by Four Heptagons: Efficient Synthesis and Properties - Borrisov, Boris; Beneventi, Giovanni Mariano; Fu, Yubin; Qiu, Zhen Lin; Komber, Hartmut; Deng, Qing Song; Greißel, Phillip; Cadranel, Alejandro; Guldi, Dirk Michael; Ma, Ji; Feng, Xinliang (Journal of the American Chemical Society, 2024)
The construction of multiple heptagonal rings in nanographene is the key step for obtaining exotic carbon nanostructures with a negative curvature and intriguing properties. Herein, a novel saddle-shaped nanographene (1) with four embedded heptagons is synthesized via a highly efficient one-shot Scholl reaction from a predesigned oligophenylene precursor. Notably, a quadruple [6]helicene intermediate was also obtained and isolated by controlling the Scholl reaction conditions. Interestingly, the single crystal structures of 1 display a saddle geometry induced by the four embedded heptagons, resulting in a deep curvature with a width of 16.5 Å and a depth of 8.0 Å. Theoretical calculations at the molecular level suggest a weak antiaromatic character of the heptagons in 1. Remarkably, compound 1 exhibits dual fluorescence from S1 and S2. The deep-saddle-shaped geometry in 1 defines host-guest interactions with fullerenes, which were explored in titration experiments and by theoretical methods. The resulting 1@C60 are stable and are subject to an electron transfer from photoexcited 1 to C60. Our current study underscores the influence of heptagon rings on the photophysical, self-assembly, and electron-donating properties of NGs.
CRIS-Team Scopus Importer:2024-10-18

Intramolecular Singlet Fission in Individual Graphene Nanoribbons─Competition with a Charge Transfer - Greißel, Phillip; Beneventi, Giovanni Mariano; Weiß, René; Wollny, Anna-Sophie; Dubey, Rajeev K.; Melle-Franco, Manuel; Clark, Timothy; Mateo-Alonso, Aurelio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2025)
Graphene nanoribbons (NRs) constitute a versatile platform for developing novel materials, where their structure governs their optical, electronic, and magnetic properties while also shaping their excited-state dynamics. Here, we investigate a set of three twisted N-doped molecular NRs of increasing length, obtained by linearly fusing perylene diimide to pyrene and pyrazino- or thiadiazolo-quinoxaline residues. By employing various temperature-dependent time-resolved spectroscopy techniques, we reveal how the flexible twisted NR geometry promotes the formation of a mixed electronic state with varying contributions from locally excited and charge-transfer (CT) states. The fate of this mixed state is highly sensitive to the molecular geometry, length, and solvent polarity. For the shortest NR, intersystem crossing dominates the deactivation pathway, efficiently generating triplets in low-polarity solvents. In contrast, for the extended NRs, intramolecular singlet fission (SF) takes place within a single nanoribbon. This is enabled by enhanced superexchange coupling due to a pronounced push-pull nature and the existence of multiple localized π-electron states caused by heteroatom doping, thereby circumventing the need for dimeric interactions typically associated with conventional SF systems. In higher-polarity environments, evidence of a (diabatic) CT state emerges. These findings underscore the intricate relationship between geometry, energy levels, and excited-state dynamics in twisted N-doped NRs.
CRIS-Team Scopus Importer:2025-04-01

Intramolecular Triplet Diffusion Facilitates Triplet Dissociation in a Pentacene Hexamer - Greißel, Phillip; Thiel, Dominik; Gotfredsen, Henrik; Chen, Lan; Krug, Marcel; Papadopoulos, Ilias; Miskolzie, Mark; Torres, Tomás; Clark, Timothy; Brøndsted Nielsen, Mogens; Tykwinski, Rik R.; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2024)
Triplet dynamics in singlet fission depend strongly on the strength of the electronic coupling. Covalent systems in solution offer precise control over such couplings. Nonetheless, efficient free triplet generation remains elusive in most systems, as the intermediate triplet pair 1(T1T1) is prone to triplet-triplet annihilation due to its spatial confinement. In the solid state, entropically driven triplet diffusion assists in the spatial separation of triplets, resulting in higher yields of free triplets. Control over electronic coupling in the solid state is, however, challenging given its sensitivity to molecular packing. We have thus developed a hexameric system (HexPnc) to enable solid-state-like triplet diffusion at the molecular scale. This system is realized by covalently tethering three pentacene dimers to a central subphthalocyanine scaffold. Transient absorption spectroscopy, complemented by theoretical structural optimizations and steady-state spectroscopy, reveals that triplet diffusion is indeed facilitated due to intramolecular cluster formation. The yield of free triplets in HexPnc is increased by a factor of up to 14 compared to the corresponding dimeric reference (DiPnc). Thus, HexPnc establishes crucial design aspects for achieving efficient triplet dissociation in strongly coupled systems by providing avenues for diffusive separation of 1(T1T1), while, concomitantly, retaining strong interchromophore coupling which preserves rapid formation of 1(T1T1).
CRIS-Team Scopus Importer:2024-02-23
Keywords: Oligoacene; Photoenergy Conversion; Singlet Fission; Triplet Dissociation; Ultrafast Spectroscopy

Molecular Acenes for Light Capture, Conversion, and Storage - Greißel, Phillip; Wollny, Anna-Sophie; Bo, Yifan; Thiel, Dominik; Weiß, René; Guldi, Dirk Michael (Accounts of Materials Research, 2024)
Conspectus Efficient photovoltaics (PV) require capturing and converting solar energy across a broad range of energy. Losses due to thermalization and sub-bandgap photons place, however, significant boundaries on the performance of solar cells. For conventional single-junction cells, the theoretical maximum power conversion efficiency is capped at 33%, a constraint known as the detailed balance limit. Realizing the full potential of PVs requires developing novel strategies to overcome this fundamental obstacle. This Account describes the photon-management capabilities of acenes and addresses these fundamental losses en-route toward enhancing PV performances. For high-energy photons that exceed the semiconductor’s bandgap energy, singlet fission (SF) is a down-conversion pathway to mitigate thermalization losses. SF is a process in organic materials, in which a singlet excited state is split into two independent triplet excited states, effectively doubling the number of charge carriers. Pentacenes stand out among acenes due to their exergonic nature of SF. Numerous molecular pentacene dimers have been synthesized to elucidate the relationship between structure and enhancing SF efficiency. A broader light-harvesting range of SF materials is realized by covalently attaching complementary absorbing energy donors to set up energy donor-acceptor conjugates. Förster resonance energy transfer (FRET) is operative in these energy donor-acceptor conjugates, effectively extending the absorption of SF materials, as the energy donor efficiently transfers its absorbed excitation energy to the energy acceptor. Our studies on various binding motifs show that FRET efficiency depends not only on parameters like the energy donor-acceptor distance and spectral overlap but also on subtle factors such as the alignment of transition dipoles, which significantly affect the energy transfer dynamics and efficiency. Turning to low-energy photons, triplet-triplet annihilation up-conversion (TTA-UC) provides a means of light up-conversion and, thereby, the reduction of sub-bandgap losses. In TTA-UC, a singlet excited state that is potent enough to generate charge carriers is formed by combining two triplet excitons. It is effectively the reverse process of SF. The higher triplet energy of tetracene and an endergonic SF renders them highly effective for TTA-UC. We focus on various tetracene-based systems that maximize TTA-UC efficiency. Besides TTA-UC, two-photon absorption (TPA) is yet another mechanism to leverage below-bandgap photons. It is a nonlinear optical (NLO) process, and acenes reveal NLO properties that are essential for extending light absorption into the near-infrared and still powering SF. We demonstrate in our proof-of-concept studies how TPA further broadens the application potential of acenes for PV systems. The strategies outlined in this Account illustrate that acenes are valuable for addressing mechanistic losses in conventional solar cells. In the final section, we examine light storage following SF by means of interfacial electron transfer. Efficient charge-injection powered by SF materials still requires more research before being implemented in large-scale PV designs. Overall, the advances discussed in this Account not only highlight the pivotal role of acenes as model systems to investigate photon down- and up-conversion processes but also paint a promising picture that more efficient solar energy conversion schemes exceeding the detailed-balance limit can be realized by implementing these materials.
CRIS-Team Scopus Importer:2025-02-04

Sensitized Singlet Fission in Rigidly Linked Axial and Peripheral Pentacene-Subphthalocyanine Conjugates - Gotfredsen, Henrik; Thiel, Dominik; Greißel, Phillip; Chen, Lan; Krug, Marcel; Papadopoulos, Ilias; Ferguson, Michael J.; Nielsen, Mogens Brøndsted; Torres, Tomas; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Journal of the American Chemical Society, 2023)
The goal of harnessing the theoretical potential of singlet fission (SF), a process in which one singlet excited state is split into two triplet excited states, has become a central challenge in solar energy research. Covalently linked dimers provide crucial models for understanding the role of chromophore arrangement and coupling in SF. Sensitizers can be integrated into these systems to expand the absorption bandwidth through which SF can be accessed. Here, we define the role of the sensitizer-chromophore geometry in a sensitized SF model system. To this end, two conjugates have been synthesized consisting of a pentacene dimer (SF motif) connected via a rigid alkynyl bridge to a subphthalocyanine (the sensitizer motif) in either an axial or a peripheral arrangement. Steady-state and time-resolved photophysical measurements are used to confirm that both conjugates operate as per design, displaying near unity energy transfer efficiencies and high triplet quantum yields from SF. Decisively, energy transfer between the subphthalocyanine and pentacene dimer occurs ca. 26 times faster in the peripheral conjugate, even though the two chromophores are ca. 3 angstrom farther apart than in the axial conjugate. Following a theoretical evaluation of the dipolar coupling, Vdip2, and the orientation factor, kappa 2, of both the axial (Vdip2 = 140 cm-2; kappa 2 = 0.08) and the peripheral (Vdip2 = 724 cm-2; kappa 2 = 1.46) arrangements, we establish that this rate acceleration is due to a more favorable (nearly co-planar) relative orientation of the transition dipole moments of the subphthalocyanine and pentacenes in the peripheral constellation.
CRIS-Team WoS Importer:2023-05-19